2020
DOI: 10.1121/10.0001698
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation context does not drive F0 lowering following voiced stops: Evidence from French and Italian

Abstract: Consonant-intrinsic F0 (CF0) effects are mainly the result of raising F0 following voiceless obstruents, rather than of lowering F0 following voiced obstruents. However, there are also documented instances where lowered F0 following voiced obstruents is enhanced. Given that both voicing and F0 are affected by prosodic context, it is possible that CF0 is lowered in some contexts but not others. This possibility is investigated by examining CF0 in French and Italian in isolated citation forms. Results are compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The present study is a further effort to improve the understanding of consonantal perturbation of F0. Recent studies (Hanson, 2009;Kirby and Ladd, 2016;Kirby et al, 2020) have already shown reduced support for the simple rise-fall dichotomy of F0 movement after voiced versus voiceless consonants (Hombert et al, 1979) illustrated in Figure 1. These studies have demonstrated the importance of using F0 of syllables with sonorant onsets as baseline when assessing the perturbation effect by obstruent consonants.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The present study is a further effort to improve the understanding of consonantal perturbation of F0. Recent studies (Hanson, 2009;Kirby and Ladd, 2016;Kirby et al, 2020) have already shown reduced support for the simple rise-fall dichotomy of F0 movement after voiced versus voiceless consonants (Hombert et al, 1979) illustrated in Figure 1. These studies have demonstrated the importance of using F0 of syllables with sonorant onsets as baseline when assessing the perturbation effect by obstruent consonants.…”
Section: Discussionmentioning
confidence: 94%
“…Aligning the F0 contours at syllable onset (Figure 7b) results in variations at the end of the syllable and the following contexts. When the F0 contours are aligned at both vowel onset and offset (Figure 7c), as done in Kirby and Ladd (2016), Kirby et al (2020), and Gao and Arai (2019), the amount of cross-consonant F0 difference is as large as in Figure 7a. Time normalizing F0 curves between the onset and offset of the target syllable (Figure 7d) seems to exhibit the least variable F0 patterns across consonant types both within the target syllable and in the surrounding carrier sentences.…”
Section: A Graphical Comparison Of F0 Contoursmentioning
confidence: 91%
See 2 more Smart Citations
“…Informative priors can also specify likely values of a population-level effect. Kirby et al (2020) estimate the effect of preceding consonant voicing on F0 in French and Italian using using an informative prior encoding the effect's likely direction and magnitude, based on previous cross-linguistic studies (see also Labuschagne and Ciocca, 2020;Vasishth et al, 2018). This approach leverages the phonetics literature for more precise estimates.…”
Section: Strongly Informative Priorsmentioning
confidence: 99%